Kontribusi Teori Belajar Kognitif Jean Piaget Pada Prestasi Belajar PAK di SDS RK Mutiara Gunung Sitoli - Lay, Sergius; Ndoa, Paulus Kanisius; Br. Panjaitan, Sonia Pratika Elisabeth (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2024)
This study was motivated by the researcher's concern about educators who pay less attention to cognitive aspects and are less creative in carrying out the learning process in the classroom so that it affects the results of learning achievement. The purpose of this study is to examine the contribution of Jean Piaget's cognitive learning theory to student learning outcomes, especially in learning Catholic religious education at SD RK Mutiara Gunungsitoli. Qualitative research using a thematic approach was used as the research method. The research site and subjects were selected by targeted sampling. Data analysis was conducted in 3 stages: data reduction, data presentation and data validation. The theoretical foundation is based on the explanation of cognitive learning theory, the application of Catholicism in religious education and its contribution to the achievement of educational outcomes. Based on the research conducted, it was found that teachers apply cognitive learning theory to students. Teachers adhere to Catholic religious education learning strategies and teaching and learning methods to improve student learning outcomes. The application of cognitive learning theory from Jean Piaget contributes to the formation of intellectual or intellect, especially in learning achievement.